DEVELOPMENT OF THE PROFESSIONAL AND METHODOLOGICAL CAPACITY OF FUTURE COMPUTER SCIENCE TEACHERS THROUGH THE USE OF INFORMAL EDUCATION TECHNOLOGIES (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article analyzes the didactic potential of informal education technologies in developing the professional and methodological capacity of future computer science teachers. The importance of informal education in ensuring continuous professional development of teachers within the modern digital educational environment is highlighted, and its main forms and tools are described. The study examines the impact of educational activities organized through online learning platforms, open educational resources, professional communities, webinars, and social networks on the development of professional competence among future computer science teachers. Furthermore, it is substantiated that the use of informal education technologies contributes to the formation of self-directed learning skills, improvement of methodological training, and enhancement of digital competencies. The findings of the study may serve as a methodological basis for developing scientific and methodological recommendations aimed at improving the process of preparing future computer science teachers for professional activity.
Keywords: Informal education, future computer science teacher, professional competence, methodological competence, professional capacity, methodological capacity, self-directed learning, online learning platforms, open educational resources, continuous professional development, educational technologies.